Guided Discovery Learning for Equitable Islamic Cultural History Learning in a Rural Indonesian Islamic Junior Secondary School: A Classroom Action Research - Suci Prastiwi; Nispi Syahbani (WISE Pendidikan Indonesia, 2026)
Teacher-centred instruction can constrain students' participation and learning in Islamic Cultural History (Sejarah Kebudayaan Islam; SKI), particularly when the subject is taught as memorization. This classroom action research examined whether guided Discovery Learning could improve participation and achievement in a Grade 8 class at a rural Indonesian Islamic junior secondary school (Madrasah Tsanawiyah; MTs). Twenty-two students participated in two planning-action-observation-reflection cycles. The intervention followed six phases: stimulation, problem identification, data collection, data processing, verification, and generalization. Observation sheets, achievement tests, interviews, and documentation were analysed descriptively using mean scores, classical mastery, and process indicators. Student activity increased from 62.21% in Cycle I to 79.09% in Cycle II, while teacher implementation rose from 68.18% to 90.90%. Mean achievement improved from 58.45 at baseline to 62.42 in Cycle I and 80.90 in Cycle II. Classical mastery increased from 40.90% to 45.45% and then 86.36%, exceeding the 80% criterion. The findings indicate that Discovery Learning becomes productive when it is explicitly scaffolded, collaboratively organised, and refined through reflection. The study contributes evidence on equitable learning opportunities in a rural madrasah context.